2012
DOI: 10.1016/j.actaastro.2012.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar communication: The case for spread spectrum

Abstract: Spread spectrum, widely employed in modern digital wireless terrestrial radio systems, chooses a signal with a noise-like character and much higher bandwidth than necessary. This paper advocates spread spectrum modulation for interstellar communication, motivated by robust immunity to radio-frequency interference (RFI) of technological origin in the vicinity of the receiver while preserving full detection sensitivity in the presence of natural sources of noise. Receiver design for noise immunity alone provides… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…By observing leakage from power beams, we may well find a message embedded on the beam. That message may use optimized power-efficient designs such as spread spectrum and energy minimization (Messerschmitt 2012(Messerschmitt , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…By observing leakage from power beams, we may well find a message embedded on the beam. That message may use optimized power-efficient designs such as spread spectrum and energy minimization (Messerschmitt 2012(Messerschmitt , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The search for wideband signals is much more challenging than the search for narrowband signals; on the other hand, a wideband beacon can carry vastly more information than a narrowband beacon. For more information on wideband SETI see, for example, papers by Benford, Benford and Benford (2010a, b); Harp et al (2011);Messerschmitt (2012); Morrison (2012).…”
Section: They Are Signaling But We Don't Know At Which Frequency To Lmentioning
confidence: 99%
“…Fridman (2011) concluded that broadband emission employing frequency-shift keying (FSK) would be preferred by energy-conscious civilizations seeking to transmit informationbearing signals using similar capabilities to our own. Messerschmitt (2012); Messerschmitt & Morrison (2012) similarly arrived at the idea that broadband communication might be preferable by considering robustness to radio frequency interference (RFI), and further deduced that this emission may have time-bandwidth extents influenced by the properties of the interstellar medium (ISM). In other words, the coherence of a modulated information-bearing signal would be limited in time or bandwidth extent by the combined effects of the relative motion of the source and receiver and the inhomogenous plasma occupying the intervening space.…”
Section: Artificial Radio Emissionmentioning
confidence: 99%